DIFFERENCES IN THE USE OF ENGLISHISM IN DAILY SPEECH IN PRIMARY SCHOOL CHILDREN IN RELATION TO SOCIODEMOGRAPHIC VARIABLES (Heritage, 2021)
Being surrounded by English leads us to think that Englishisms are found in everyday language. The subject of this paper is to examine the differences in the use of English among students of the third, fourth, and fifth grade of primary school in Kosovska Mitrovica in relation to sociodemographic variables (gender, grade and age of students, school success, educational level of parents and socioeconomic status of the family). a survey with offered words of Serbian and English origin with the aim of giving an insight into how many foreign words are used instead of domestic ones. The research found that a statistically significant difference exists only between students whose mothers are of different educational levels. Other hypotheses have not been confirmed.
Keywords: Anglicism, primary school, sociodemographic variables, English language.